Testing of Currency Substitution Effect on Exchange Rate Volatility in Serbia - Petrović, Predrag; Filipović, Sanja; Nikolić, Goran (Industrija, 2016)
Despite numerous different definitions existing in the literature, currency substitution is generally understood as a phenomenon when domestic residents prefer to use foreign currency rather than domestic currency. The main reasons for such phenomenon include high and volatile inflation, strong depreciation of national currency and high interest rate differential in favour of foreign currency. Currency substitution, as a monetary phenomenon, is widely spread in Latin American, Eastern European and some Asian countries. This paper is dedicated to the influence of currency substitution on exchange rate volatility in Serbia. The research included testing of three hypotheses: (i) currency substitution positively affects depreciation rate volatility, (ii) depreciation rate volatility has stronger responses to the past negative than to the past positive depreciation shocks, and (iii) currency substitution positively affects expected depreciation rate. The analysis was implemented for the period 2002:m1-2015:m12 (2004:m1-2015:m12), applying modified EGARCH-M model. Based on the obtained results, all three hypotheses have been supremely rejected regardless of the manner of quantification of currency substitution.